2003
DOI: 10.1002/jcla.10064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the traditional chinese medicines Chan Su, Lu‐Shen‐Wan, Dan Shen, and Asian Ginseng on Serum Digoxin measurement by Tina‐quant (Roche) and Synchron LX system (Beckman) digoxin immunoassays

Abstract: Chan Su, Lu-Shen-Wan, Dan Shen, and Asian ginseng are traditionally used to treat a number of conditions, including cardiovascular disease. All of these traditional Chinese medicines exhibit cardioactive properties. Digoxin is a cardioactive drug with a narrow therapeutic range (0.8-1.9 ng/mL). A patient taking digoxin may also take these Chinese medicines for their cardiotonic effects. Moreover, the active components of these medicines that are responsible for cardiotonic effects bear structural similarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Taking advantage of poor protein binding of digoxin (25%) and high protein binding of digoxin-like immunoreactive components of Danshen, Wahed and Dasgupta [120] and Dasgupta [121] demonstrated that the positive and negative interferences of Danshen in serum digoxin measurement can be eliminated by monitoring the free digoxin concentration. On the other hand, the EMIT 2000 (Dade Behring, Deerpark, IL) [122], Randox (Randox Labs Ltd., Antrim, UK) [122], CLIA (Bayer Diagnostics, Tarrytown, NY) [122], Tina-quant (Roche Diagnostics) [123] and Synchron LX system (Beckman) [123] immunoassays for digoxin showed no interference from Danshen.…”
Section: Digoxinmentioning
confidence: 99%
“…Taking advantage of poor protein binding of digoxin (25%) and high protein binding of digoxin-like immunoreactive components of Danshen, Wahed and Dasgupta [120] and Dasgupta [121] demonstrated that the positive and negative interferences of Danshen in serum digoxin measurement can be eliminated by monitoring the free digoxin concentration. On the other hand, the EMIT 2000 (Dade Behring, Deerpark, IL) [122], Randox (Randox Labs Ltd., Antrim, UK) [122], CLIA (Bayer Diagnostics, Tarrytown, NY) [122], Tina-quant (Roche Diagnostics) [123] and Synchron LX system (Beckman) [123] immunoassays for digoxin showed no interference from Danshen.…”
Section: Digoxinmentioning
confidence: 99%
“…However, the lower limit of quantitation of immunoassays which are commonly used method for digoxin assays (0.1-0.4 ng/mL, see Table 1) are not sensitive enough to evaluate the pharmacokinetics of digoxin administered at less than 0.25 mg such as 0.125 mg. It has been reported that immunoassays are relatively nonspecific and cross-react with digoxin metabolites and endogenous digoxin-like substances [11][12][13][14][15][16]. Recently, LC/MS/MS, which is highly sensitive and specific, has become accepted as the leading technique for the quantitation of exogenous substances in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…These Chinese medications have been widely used in China, Japan and other Asian countries for a long time, and over the last decade, have gained considerable favor in the United States and other places of the world. Toad venom is used as a topical anesthetic and cardiac medication [3,4]. It can eliminate toxic material; relieve carbuncle, furuncle, cellulites and multiple abscesses [5].…”
Section: Introductionmentioning
confidence: 99%